Mental health training, attitudes toward support, and screening positive for mental disorders. Issue 1 (2nd January 2020) - Carleton, R. Nicholas; Afifi, Tracie O.; Turner, Sarah; Taillieu, Tamara; Vaughan, Adam D.; Anderson, Gregory S.; Ricciardelli, Rosemary; MacPhee, Renée S.; Cramm, Heidi A.; Czarnuch, Stephen; Hozempa, Kadie; Camp, Ronald D.
ABSTRACT: Public Safety Personnel (PSP; e.g. correctional workers, dispatchers, firefighters, paramedics, police) are frequently exposed to potentially traumatic events (PTEs). Several mental health training program categories (e.g. critical incident stress management (CISM), debriefing, peer support, psychoeducation, mental health first aid, Road to Mental Readiness [R2MR]) exist as efforts to minimize the impact of exposures, often using cognitive behavioral therapy model content, but with limited effectiveness research. The current study assessed PSP perceptions of access to professional (i.e. physicians, psychologists, psychiatrists, employee assistance programs, chaplains) and non-professional (i.e. spouse, friends, colleagues, leadership) support, and associations between training and mental health. Participants included 4, 020 currently serving PSP participants. Data were analyzed using cross-tabulations and logistic regressions. Most PSP reported access to professional and non-professional support; nevertheless, most would first access a spouse (74%) and many would never, or only as a last resort, access professional support (43–60%) or PSP leaders (67%). Participation in any mental health training category was associated with lower ( p < .01) rates for some, but not all, mental disorders, with no robust differences across categories. Revisions to training programs may improve willingness to access professional support; in the interim, training and support for PSP spouses and leaders may also be beneficial.